2018
DOI: 10.5543/tkda.2018.65960
|View full text |Cite
|
Sign up to set email alerts
|

Early and mid-term outcomes after surgical repair of congenital supravalvular aortic stenosis by Doty technique

Abstract: The Doty technique is an anatomically and technically effective surgical approach to treating SVAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Previous studies indicated that preoperative combined pulmonary stenosis, PVS, and bicuspid aortic valve were risk factors for adverse events in the surgical treatment of SVAS [ 4 , 19 ]. In addition, the mortality rate was lower compared with other centers (3.1–10%) [ 20 , 21 , 22 ]. Therefore, considering the poor preoperative baseline in the pericardium patch group, the pericardium patch performed acceptably in terms of safety.…”
Section: Discussionmentioning
confidence: 67%
“…Previous studies indicated that preoperative combined pulmonary stenosis, PVS, and bicuspid aortic valve were risk factors for adverse events in the surgical treatment of SVAS [ 4 , 19 ]. In addition, the mortality rate was lower compared with other centers (3.1–10%) [ 20 , 21 , 22 ]. Therefore, considering the poor preoperative baseline in the pericardium patch group, the pericardium patch performed acceptably in terms of safety.…”
Section: Discussionmentioning
confidence: 67%
“…11 The Doty technique and Brom technique are seen as more preferred in SVAS surgery throughout recently published articles from Türkiye. 12 Koçyildirim et al found no significant difference between the two techniques in an SVAS article, in which single-patch and three-patch techniques were compared. 13 Bostan et al reported that reoperation was required for a patient who underwent single-patch surgery during the follow-up period.…”
Section: Discussionmentioning
confidence: 98%
“…After reviewing titles and abstracts, 41 citations remained for the full-text screening and 71 records were deleted due to irrelevance to our study. Finally, 27 studies (7, 8,11,14,[16][17][18][19][20][21][22][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] were included.…”
Section: Eligible Studiesmentioning
confidence: 99%